Comparative Gross Anatomical Studies on the Testes of Zovawk (Mizo Local Pig) and Large White Yorkshire Pig - Singh, T. Shitarjit; Kalita, P. C.; Kalita, A.; Doley, P. J.; Choudhary , O. P.; Rozami, V. L. (International Journal of Livestock Research, 2019)
The study was conducted on 12 apparently healthy pigs, out of which 6 were Zovawk (Mizo local pig) and 6 (six) were Large White Yorkshire pig. The testes of both type of pigs were reddish white in colour. They were elliptical and rounded to oval in shape in Zovawk and Large White Yorkshire pig. The long axis of the testis was oblique in Zovawk and slightly horizontal in Large White Yorkshire pig. The different biometrical values in regard to weight, length, width and thickness were found to be higher in left side of testis than the right side in Zovawk and Large White Yorkshire Pig. The average Net weight of the right and left testicles of adult Zovawk was 42.85±4.88 gm and 43.93±3.54 gm and that of Large White Yorkshire was 259.57±32.22 gm and 269.52±27.22 gm, respectively. These biometrical parameters were found to be low in Zovawk as compare to Large White Yorkshire pig.